Answer:
x=-3/19
y=39/19
Explanation:
the equations can be written as the following system
![x+3y=6\\-12x+2y=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/u4y6ynlnl49brws5pn4fscld4x7d9l2k5j.png)
If the second equation is multiplied by 3/2 it will become -18x+3y=9
If that equation is then subtracted with the first you will obtain the following
-19x=3, it means x=-3/19
The other variable is obtained by substituting the new value for x in the first equationx+3y=6, thus we obtain that y=39/19